Gut microbiota differences between sports and non-sports major students: a population-controlled trial - Benlong Ma; Yifang Zhang; Wenbo Yuan; Nan Hu; Shanshan Li (AIMS Bioengineering)
Physical exercise contributes to good health and affects gut microbiota. We investigated the gut microbiota features of students majoring in sports. Fecal samples were collected from the sports majors (SS group, 50 students, 11 males, and 39 females, 18.7 ± 0.8 years old) and non-sports majors (NC group, 50 students, 23 males, and 27 females, 19.0 ± 1.0 years old) for high-throughput sequencing analysis. Their clinical data were statistically analyzed. The results showed that the gut microbiota compositions are similar in evolution and development, and significant differences were observed in the proportion of rare species, such as Fusobacterium, Mitsuokella, Acidaminococcus, and Butyricicoccus. Compared with the NC group, the SS group exhibited a more diverse gut microbiota, with a high abundance of Alistipes, Faecalibacterium, Roseburia, Prevotella, etc., at the genus level, as well as Faecalibacterium prausnitzii, Bifidobacterium adolescentis, Bacteroides uniformis, and Bacteroides plebeius at the species level. The research shows that long-term physical exercise or training can enhance gut microbiota diversity and boost beneficial bacteria, which are conducive to intestinal environmental conditions.